Mitomycin-treated undifferentiated embryonic stem cells as a safe and effective therapeutic strategy in a mouse model of Parkinson’s disease - Acquarone, Mariana; de Melo, Thiago M.; Meireles, Fernanda; Brito-Moreira, Jordano; Oliveira, Gabriel; Ferreira, Sergio T.; Castro, Newton G.; Tovar-Moll, Fernanda; Houzel, Jean-Christophe; Rehen, Stevens K. (Frontiers in Cellular Neuroscience, 2015)
Parkinson’s disease (PD) is an incurable progressive neurodegenerative disorder. Clinical presentation of PD stems largely from the loss of dopaminergic neurons in the nigrostriatal dopaminergic pathway, motivating experimental strategies aimed at replacing dopaminergic innervation by cellular therapy. Transplantation of dopaminergic neurons derived from embryonic stem cells significantly improves motor functions in rodent and non-human primate models of PD. However, protocols to generate dopaminergic neurons from embryonic stem cells generally meet with low efficacy and high risk of teratoma development upon transplantation. To address these issues, we have pre-treated undifferentiated mouse embryonic stem cells (mESCs) with the DNA alkylating agent mitomycin C (MMC) before transplantation. MMC treatment of cultures prevented tumor formation in a 12-week follow-up after mESCs were injected in nude mice. In 6-OH-dopamine-lesioned mice, intrastriatal injection of MMC-treated mESCs markedly improved motor function without tumor formation for as long as 15 months. Furthermore, we show that halting mitotic activity of undifferentiated mESCs induces a four-fold increase in dopamine release following in vitro differentiation. Our findings indicate that treating mESCs with mitomycin C prior to intrastriatal transplant is an effective strategy that could be further investigated as a novel alternative for treatment of Parkinson's disease.